The role of liquid smoke coconut shell in the proliferation phase of an oral traumatic ulcer - Nurina Febriyanti Ayuningtyas; Meircurius Dwi Condro Surboyo; Diah Savitri Ernawati; Adiastuti Endah Parmadiati; Hening Tuti Hendarti; Fatma Yasmin Mahdani; Saka Winias; Fitriatuz Zakia; Indira Arella Harianto (GarVal Editorial Ltda., 2020)
Context: Liquid smoke coconut shell (LS-CS) contains phenolic compounds that are able to promote wound healing by interfering with the inflammation phase of wound healing. The homeostatic mechanism that decreases the inflammation releases a growth factor that enhances proliferation by increasing fibroblast growth factor-2 (FGF-2), vascular endothelial growth factor (VEGF) expression and fibroblast proliferation. Aims: To analyze the role of LS-CS in the proliferation phase of oral traumatic ulcer healing by analyzing fibroblast numbers and FGF-2 and VEGF expressions. Methods: Oral traumatic ulcers were induced in diabetes mellitus Wistar rats via an alloxan injection. A traumatic ulcer as long as 10 mm was made in the inferior fornix incisive labial area. The oral traumatic ulcer was then topically treated with LS-CS using a dose of 20 μL/ 20 g body weight once daily for three, five and seven days. The fibroblast number of the oral traumatic ulcers' tissue was then analyzed using hematoxylin-eosin, and the FGF-2 and VEGF expression were analyzed via immunohistochemistry staining. The difference in fibroblast numbers and FGF-2 and VEGF expressions were analyzed by one-way ANOVA and post hoc tests with a significance of p<0.05. Results: The LS-CS affected fibroblast numbers (p=0.001) and FGF-2 expression (p=0.000) after topical treatment for seven days. There was a significant difference in the expression of VEGF after topical treatment with LS-CS for five days compared to the control group (p=0.000) and benzydamine hydrochloride (p=0.005). The topical treatment of LS-CS for seven days affected the expression of VEGF compared to the control group (p=0.000) and benzydamine hydrochloride (p=0.019). Conclusions: LS-CS could improve the healing of oral traumatic ulcers by increasing fibroblast numbers and FGF-2 and VEGF expression after seven days of treatment.